Risk Factors for Low Birth Weights of Pregnant Women Receiving Prenatal Care at Yan Ta Khao Hospital - Rongdech, Sinchai; Akkarasuwankul, Anan (Journal of Health Science of Thailand, 2017)
The objective of this cross-sectional descriptive study was to find out the factors influencing low birth weight of newborns and its incidence for the sake of controlling, improving and solving the low birth weight problems of newborns as well as supporting further development plan of maternal and child health promotion. In this study, 422 cases of pregnant women receiving pre and post natal care at Yan Ta Khao hospital, Trang province were included. Several independent variables including 1) fundamental information of mother (before pregnancy weight, education, occupation, religion, marital status, history of abortion, underlying diseases) and 2) the factors related to medical and health care during pregnancy (gestational age of the first prenatal care, pregnant weight gain, a number of prenatal cares, hematocrit of the first prenatal care, antenatal hematocrit, pregnancy complications and gestational age at birth) were statistically analyzed with respect to the weights of newborn infants as a dependent variable. Descriptive statistics, chi-square, odds ratio and 95%CI were used in data analysis. The results reveal that the average age of the pregnant women was 26 years, while those with the age below 20 years accounted for 20.4 percent. Most of them were Buddhist and in a farming with high school graduates and living with husbands (94.5%). It was reported that 42.9 percent were primipara and 17.1 percent had history of abortion. Anemia and asthma were the first and second underlying diseases accounting for 2.1 percent and 1.4 percent, respectively. With respect to gestational ages of the first prenatal care, 64.2 percent of them were lower than 12 weeks. The pregnant women with the weights before pregnancy lower than 45 kilograms accounted for 14.7 percent. Of all cases, 99.1 percent received prenatal care more than or equal to 4 times. There were 14.9 percent which hematocrit at birth lower than 33 percent. The most complications found during pregnancy were anemia (14.5%), and the proportion of gestational age at delivery below 36 weeks were only 0.9 percent. There were 35.1 percent which their weights gained during pregnancy below 10 kilograms. The incidence of lower-birth weight than 2,500 grams was only 8.8 percent. The factors which statistically related significantly to low birth weight at 95% confidence interval, were pre-pregnancy weights less than 45 kilograms (p 0.001, OR 3.007, 95%CI 1.425, 6.346), pregnant weight gained lower than 10 kilograms (p 0.002, OR 2.666, 95%CI 1.345, 5.285), hematocrit at delivery (p 0.004, OR 2.709, 95%CI 1.263, 5.811) and gestational age at delivery lower than 36 weeks (p 0.001, OR 10.943, 95%CI 1.495, 80.07). To prevent low birth weight, it should therefore emphasize both maternal care before pregnancy to gain weight greater than or equal to 45 kilograms and antenatal care to gain weight at least 10 kilograms during pregnancy and to have hematocrit higher than 33 percent as well as to take care of gestational age at delivery greater than 36 weeks.